2013
DOI: 10.1038/jcbfm.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Analysis of Arterial, Venous, and CSF Flows using Phase-Contrast MRI: A Quantitative Comparison Between MS Patients and Healthy Controls

Abstract: Venous dysfunction has recently been hypothesized to contribute to the pathophysiology of multiple sclerosis (MS). 2D phasecontrast (PC) magnetic resonance imaging (MRI) is a non-invasive and innocuous technique enabling reliable quantification of cerebrospinal fluid (CSF) and blood flows in the same imaging session. We compared PC-MRI measurements of CSF, arterial and venous flows in MS patients to those from a normative cohort of healthy controls (HC). Nineteen MS patients underwent a standardized MR protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 39 publications
10
52
1
1
Order By: Relevance
“…Our results, when comparing patients with MS and HC without taking into account the possible effect of stenosis, are in line with most, 15,18,20,30 but not all, 19 previous studies. A possible explanation for this discrepancy may be the inclusion of patients with MS with progressive subtypes in the study by Sethi et al 19 Indeed, Feng et al 16 showed that the tAF of progressive forms were different from the tAF observed in RR-MS; thus, the normalization of IJV flows to tAF, which is different between the two subgroups, could explain this discrepancy.…”
Section: Full Paper: No Evidence Of Extracranial Venous Abnormalitiessupporting
confidence: 78%
See 3 more Smart Citations
“…Our results, when comparing patients with MS and HC without taking into account the possible effect of stenosis, are in line with most, 15,18,20,30 but not all, 19 previous studies. A possible explanation for this discrepancy may be the inclusion of patients with MS with progressive subtypes in the study by Sethi et al 19 Indeed, Feng et al 16 showed that the tAF of progressive forms were different from the tAF observed in RR-MS; thus, the normalization of IJV flows to tAF, which is different between the two subgroups, could explain this discrepancy.…”
Section: Full Paper: No Evidence Of Extracranial Venous Abnormalitiessupporting
confidence: 78%
“…Venous structures, owing to their anatomical properties, show a high intersubject variability, 15 even depending on the body position in which these structures are studied. 11 The presence of venous flow abnormalities in MS has been widely investigated during the last years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that the degree of mean flow velocity (mFV) would reflect the degree of flow volume change. Normal ICA flow was assumed to be 270±35 cm 3 /min (4.5 ±0.6 cm 3 /s) [6]. TCD was performed before and after guiding catheter (7Fc envoy, Codman, Shurtleff, Inc.) insertion and before and after saline infusion using a pressure bag (300 mmHg).…”
Section: Mini-experimentsmentioning
confidence: 99%